QUANTITATIVE ASSESSMENT OF NITROGEN AND PHOSPHORUS CONTENTS IN HYDERABAD CITY SEWAGE AND FuLELI CANAL WATER (Biological Sciences - PJSIR, 2002)
Fulleli canal takes off from left bank of river Indus at Kotri  barrage  and  passes through  Hydetabad  city, where untreated  and partially treated city sewage is added. Five samples from  sewage and seven  samples along Fuleli  canal  were collected  for three years at an interval of 4 to 6 weeks. These samples were analysed for nitrogen  (organic, ammonia, nitrite, nitrate)  and phosphorou s (ortho, conden sed and  total  phosphate). The variation  in the concentration  of total  nitrogen  ranged  from22.6 to 99.2 mg L- 1 and 4.4 to 42.8 mg L- 1 and phosphorous ranged 2.6 to 44 . 1 mg L-1 and 0.041 to 15.94 mg L- 1 in  sewage and along Fuleli canal respectively. The amount of nitrogen and phosphorou s added to Fuleli canal from sewage  water  were calculated  to 316.2 and  85.3 tons/month  .